THE PREVALANCE OF HELICOBACTER PYLORI IN DIFFERENT UPPER GASTROINTESTINAL SYSTEM DISEASES - Vedat GÖRAL; Mine TURHANOĞLU; Halil DEĞERTEKİN and Eralp ARIKAN and Nursen KADAYIFÇIOĞLU and Nevzat AKSOY and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2020)
-